Early development of infants born prematurely who were conceived through assisted reproductive technologies - Vesna Pavlović; Aleksandra Stojadinović; Georgios Konstantinidis; Katarina Katić (Elsevier, 2024)
Objective: This study aims to determine physical and psychomotor development characteristics during the first 24 months of life in prematurely born children conceived with assistive reproductive technologies and to determine specific risk factors for deviation from typical development. Patients and methods: The study included 308 prematurely born children (154 conceived with assistive reproductive technologies - ART group and 154 conceived naturally - NC group) hospitalized at the Institute for the Health Care of Children and Adolescents of Vojvodina in Serbia. The physical and psychomotor development was monitored during the first two years of life. Results: Birth weight was statistically significantly higher in the NC group than in the ART group, and IUGR was more often present in the ART group than in the NC group of newborns. The mean values of body weight, length, and head circumference of children from both groups did not differ statistically significantly at 18 months. At 12 and 18 months, children from the ART group significantly more often had below-average scores on the test for assessment of psychomotor development (corrected GDQ <90) than children from the NC group, but not at 24 months. Logistic regression analysis has shown that at 12 and 18 months, multiple pregnancy is an independent risk factor for lower GDQ. Conclusion: At the age of 12 months, prematurely born children conceived with ART do not differ in physical development from prematurely born children after natural conception. At 12 and 18 months, prematurely born children conceived with ART achieve lower global developmental scores than children conceived naturally, but not at 24 months of age. Multiple pregnancies are an independent risk factor for lower achievement on the test for assessment of psychomotor development in prematurely born children.